Determination of saturated and unsaturated fatty acids amount in leukocyte membranes from subjects fed with solid and fluid oils - Erman, Fazilet; Aydin, Suleyman; Demir, Yasar; Akcay, Fatih; Bakan, Ebubekir (The Biochemical Society of the Republic of Korea, 2006)
Modifications in dietary fatty acid intake might lead to a modification in membrane phospholipid fatty acid composition. The purpose of this study was to investigate relationship between different type of oil consumption and leukocyte membrane phospholipid composition. This study was carried out in subjects utilizing butter (n = 15), margarine (n = 15), fluid oil (n = 15) and mixed types of oils (n = 15) in total 60 subjects. Leukocytes were separated from total blood by dextran sedimentation method. Membrane lipids and proteins were isolated following the cell disruption. Fatty acids of membrane phospholipids were isolated by hydrolysation with phospholipase B under ultrasonic dismembranator. Free fatty acids were identified with gas chromatography at chloroform phase. The results obtained were compared with data obtained by chromatograms of the standards. Results more prominent values of arachidic, dihomo-?-linolenic and palmitoleic acids were found in butter-or mixed oil-user groups; eicosadienoic, eicosamonoenoic, dihomo-?-linolenic and behenic acids in fluid oil; heptanoic, valeric, eicosadienoic and linolenic acids in margarine groups. The fatty acid composition of mixed oil was similar to butter, while other two oils were so different. From this study, it was concluded that the type of oil consumption might have an influence on phospholipid components of plasma membranes.
Keywords: Fatty acid; Membrane; Oil